Dystocia due to polymelia calf in cattle – a case report - Arunpandian, J; Srivastava, N; Ganesan, M (Animal Reproduction Update, 2023)
The veterinarian presented a 5-year-old HF crossbred cow with a full-termpregnancy that caused severe abdominal strain. On per-vaginal examination, thecervix was found to be fully dilated, with palpable multiple limbs of the foetus.After proper lubrication of the birth canal, the foetus was successfully deliveredThe veterinarian diagnosed the condition as polymelia of the hind limbs. Thepostoperative care of the cow included treatment with antibiotics and anti-inflammatory drugs. The cow had an uneventful recovery in about 9–10 days.